Experimental Investigation of PV Array Interconnection Topologies at Nonuniform Aging Condition for Power Maximization (GUB Journal of Science and Engineering, 2020)
In vast Photovoltaic (PV) power plant the output power production decreases significantly due to the fact of non-uniform aging of PV modules. The non-uniform aging of PV modules increases current-voltage (I-V) mismatch among the array modules and causes mismatch power loss (MPL). There are different interconnection topologies of the PV module in an array to minimize MPL and thus maximize the array output power. This paper investigates four different interconnection topologies experimentally on a 4×4 nonuniformly aged PV array. Three different patterns of PV module rearrangement are used to investigate the performance of each interconnection topology in terms of array output power and MPL. The experimental results show that the proposed interconnection topology is yields about 3.28% (average) higher output power than that of the most commonly used series-parallel array topology.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 6(1), Dec 2019 P 39-45